American Protestantism in the age of psychology - Muravchik, Stephanie, 1970- (Cambridge ; New York : Cambridge University Press, 2011)
"The social history of three major psycho-spiritual movements since World War II shows that these groups innovated a practical religious psychology that nurtured participants' faith, fellowship, and responsibility"--Provided by publisher.
"Many have worried that psychology has corrupted American faith, eroded citizens' virtue, and weakened its community life. But the social history of three major psycho-spiritual movements since World War II--Alcoholics Anonymous, The Salvation Army's outreach to homeless men, and the "clinical pastoral education" movement finds the opposite. These groups innovated a practical religious psychology that nurtured participants' faith, fellowship, and personal responsibility. This is one of the first works to have found a positive role for psychology in bolstering American religious and democratic life. It is also perhaps the only book in the history of religion and psychology to base its arguments on the effect of psycho-spiritual programs on its subjects' actual lives over time"--Provided by publisher.
Machine generated contents note: Introduction: 1. The fall and rise of psychoreligious cooperation; Part I. Therapy as Ministry in Clinical Pastoral Education: 2. The priest must drink at the scientific well; 3. Being the love of God; Part II. Therapy as Fellowship in Alcoholics Anonymous: 4. Democracy is a therapy; 5. Came to believe; Part III. Therapy as Evangelism in the Salvation Army: 6. Freud is not a suitable psychologist; 7. New creatures in Christ; Conclusion: 8. American psychology in an age of faiths.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Pastoral psychology -- United States -- History; Protestant churches -- United States -- History; Clinical pastoral education (Movement) -- History; Alcoholics Anonymous -- History; Church work with men -- Salvation Army -- History; RELIGION / Christian Ministry / Counseling & Recovery; Electronic books